Systematics of first 2$^+$ state g factors around mass 80 - Mertzimekis, T. J.; Stuchbery, A.E.; Benczer-Koller, N.; Taylor, M.J. (Phys. Rev. C, 2003)
The systematics of the first 2+ state g factors in the mass 80 region are investigated in terms of an IBM-II analysis, a pairing-corrected geometrical model, and a shell-model approach. Subshell closure effects at N = 38 and overall trends were examined using IBM-II. A large-space shell-model calculation was successful in describing the behavior for N=4 and N=50 nuclei, where single-particle features are prominent. A schematic truncated-space calculation was applied to the lighter isotopes. The variations of the effective boson g factors are discussed in connection with the role of F-spin breaking, and comparisons are made between the mass 80 and mass 180 regions.